2023
DOI: 10.1021/jacs.2c11684
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Cyclization to Large Peptidomimetic Macrocycles by In Situ-Generated β-Turn-Enforced Folding

Abstract: Macrocycles have been targets of extensive synthetic efforts for decades because of their potent molecular recognition and self-assembly capabilities. Yet, efficient syntheses of macrocyclic molecules via irreversible covalent bonds remain challenging. Here, we report an efficient approach to large peptidomimetic macrocycles by using the in situ-generated β-turn structural motifs afforded in the amidothiourea moieties from the early steps of the reaction of 2 molecules of bilateral amino acid-based acylhydrazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…This is largely a result of the well-known difficulty of achieving selective intramolecular coupling via end-to-end cyclization when preparing larger rings; while normal-sized ring (5–7-membered) cyclization reactions of the type 1 → 2 (Scheme A) are generally kinetically favorable, “easy” reactions, the analogous cyclization reactions to make larger ring products ( 3a → 4a ) are usually much more difficult, and are often plagued by competing intermolecular reactions (e.g., 3a → 5a , Scheme A) . High-dilution (or pseudohigh-dilution) approaches are routinely used to limit intermolecular reactions, but rarely prevent them completely, and can negatively impact the practicality and scalability of the synthesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is largely a result of the well-known difficulty of achieving selective intramolecular coupling via end-to-end cyclization when preparing larger rings; while normal-sized ring (5–7-membered) cyclization reactions of the type 1 → 2 (Scheme A) are generally kinetically favorable, “easy” reactions, the analogous cyclization reactions to make larger ring products ( 3a → 4a ) are usually much more difficult, and are often plagued by competing intermolecular reactions (e.g., 3a → 5a , Scheme A) . High-dilution (or pseudohigh-dilution) approaches are routinely used to limit intermolecular reactions, but rarely prevent them completely, and can negatively impact the practicality and scalability of the synthesis …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of macrocycles and medium-sized rings can be challenging, especially on large scales. 6 This is largely a result of the well-known difficulty of achieving selective intramolecular coupling via end-to-end cyclization when preparing larger rings; while normal-sized ring (5–7-membered) cyclization reactions of the type 1 → 2 ( Scheme 1 A) are generally kinetically favorable, “easy” reactions, the analogous cyclization reactions to make larger ring products ( 3a → 4a ) are usually much more difficult, and are often plagued by competing intermolecular reactions (e.g., 3a → 5a , Scheme 1 A). 7 High-dilution (or pseudohigh-dilution) approaches are routinely used to limit intermolecular reactions, but rarely prevent them completely, and can negatively impact the practicality and scalability of the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the asymmetric packing of molecules oriented by noncovalent forces in the self-assembly exhibits chirality at the supramolecular scale, which correlates to the generation of versatile chiral nano/microarchitectures and other selfassemblies of diverse dimensions and sizes. 4 Compared to the synthetic chemistry that produces chiral molecules by asymmetric catalysis or resolution, the supramolecular protocol is efficient as it works by assembling chiral molecules or through symmetry breaking with subsequent chiral amplication. [5][6][7] The various noncovalent forces allow exible design and fabrication of chiral-assembled structures towards advanced functions and applications for asymmetric sensing, recognition, resolution, and chiroptical materials.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid–liquid extraction (LLE) is a relatively fast and feasible methodology for anion separation that can be integrated with industry-available equipment compared to chemical precipitation/crystallization. 21–24 A few reports found that H 2 PO 4 − or HPO 4 2− could be separated from water with 80% efficiency using synthetic receptors via LLE. 25–28 Typically, these receptors were positively charged either through protonation or chelation with metals, thus facilitating strong binding affinity with phosphate.…”
mentioning
confidence: 99%